Study on Temperature and Pressure Variation of Scallop During Vacuum Freeze-drying - Zheng Lijing Guan Zhiqiang Li Min (Zhileng xuebao)
An experiment was conducted with the parameter adjustment of two-time poikilothermia and one-time variable pressure process during freezing and drying process for the adductor muscle of Chlamys Farreri.The result shows that the center temperature of the material would influence the rehydrate rate and the energy consumption of the freezing and drying sample when the temperature was changed at the first time.If the first temperature adjustment was performed,the sample rehydrate rate and the rehydrate speed of...